2016
DOI: 10.1016/j.jecp.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological correlates of attention behavior in early infancy: Implications for emotion regulation during early childhood

Abstract: Current theoretical conceptualizations of regulatory development suggest that attention processes and emotion regulation processes share common neurophysiological underpinnings and behavioral antecedents such that emotion regulation abilities may build upon early attentional skills. To further elucidate this proposed relationship, we tested whether early neurophysiological processes measured during an attention task in infancy predicted in-task attention behavior, and whether infant's attention behavior was su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 92 publications
3
24
0
1
Order By: Relevance
“…In a recent empirical paper utilizing the same dataset as the current study, we found that medial frontal 6–9 Hz EEG activity during an attention task was associated with concurrent observed attention behavior at 10 months of age (Perry et al, 2016). Interestingly, this relationship varied by hemisphere; an increase in right frontal (F4) power was associated with more time spent looking at task stimuli while an increase in power at the analogous left frontal location (F3) was associated with less time spent attending.…”
Section: Neurophysiological Underpinnings Of Attention Behaviorsupporting
confidence: 52%
See 1 more Smart Citation
“…In a recent empirical paper utilizing the same dataset as the current study, we found that medial frontal 6–9 Hz EEG activity during an attention task was associated with concurrent observed attention behavior at 10 months of age (Perry et al, 2016). Interestingly, this relationship varied by hemisphere; an increase in right frontal (F4) power was associated with more time spent looking at task stimuli while an increase in power at the analogous left frontal location (F3) was associated with less time spent attending.…”
Section: Neurophysiological Underpinnings Of Attention Behaviorsupporting
confidence: 52%
“…Taken together with our previous work, a pattern of findings emerges in which more right frontal (F4) activity during an attention task at 10 months is associated with greater attentional engagement behavior at 10 months and greater emotion regulation capabilities (less frustration) at 3 years, through its association with greater attentional abilities at 10 months. In contrast, more left frontal (F3) activity is associated less attentional engagement behavior at 10 months and less regulation (greater frustration) at 3 years, through its association with less attentional engagement at 10 months (Perry et al, 2016). Our work here demonstrates that maternal intrusiveness in the first year is one environmental factor that can predict the pattern of neural activity present during the attention task, and that this has implications for attention behavior.…”
Section: Discussionmentioning
confidence: 94%
“…The differential susceptibility framework has been supported with behavioral (Belsky, Bakermans‐Kranenburg, & van Ijzendoorn, ), genetic (van Ijzendoorn & Bakermans‐Kranenburg, ), and biological (Wagner, Mills‐Koonce, Willoughby, & Cox, in press) markers, including RSA (Peltola et al, ). Housed within the autonomic nervous system (ANS), which functions to regulate unconscious biobehavioral response (Beauchaine, ), the parasympathetic nervous system promotes homeostasis and regulates response to stress (Beuchaine, ; Perry, Swingler, Calkins, & Bell, ; Porges, ). As a measure of parasympathetic arousal, RSA reflects the variation in heart rate as it occurs at the frequency of breathing, which is controlled by the vagus nerve.…”
Section: Introductionmentioning
confidence: 99%
“…The so‐called error‐related negativity (ERN) can be observed after self‐committing errors or in response to perceived errors (Bates, Patel, & Liddle, ; Mesika, Tzur, & Berger, ). Also, source localization of the ERN shows that this potential originates in the ACC (Luu, Tucker, Derryberry, Reed, & Poulsen, ; Perry, Swingler, Calkins, & Bell, ) and is related to neural activation in the theta frequency range.…”
Section: Introductionmentioning
confidence: 99%
“…The so-called error-related negativity (ERN) can be observed after selfcommitting errors or in response to perceived errors (Bates, Patel, & Liddle, 2005;Mesika, Tzur, & Berger, 2014). Also, source localization of the ERN shows that this potential originates in the ACC (Luu, Tucker, Derryberry, Reed, & Poulsen, 2003;Perry, Swingler, Calkins, & Bell, 2016) and is related to neural activation in the theta frequency range. Berger, Tzur, and Posner (2006) studied error-related brain activity in infants and found that, similarly to adults, 7-to 9-month-olds show a fronto-central negative component around 330-560 ms following the presentation of an incorrect arithmetic operation performed with puppets.…”
mentioning
confidence: 99%